Legal Analysis of the Validity of Child Witnesses in Premeditated Murder Cases (Study of Decision No. 50/Pid.B/2023/PN Son) - Tris Seminarty Malamassam; Muhammad Arif (Faculty of Law, Universitas Muhammadiyah Sorong, 2026)
The research aims to analyze (1) the legal validity of child witness testimony under Indonesian criminal procedure law, and (2) judicial considerations in Decision Number 50/Pid.B/2023/PN Son. This research employs an empirical (socio-legal) approach with a case study method. Primary data were obtained through interviews with legal practitioners, while secondary data consisted of court decisions, statutory regulations, and relevant legal literature. Data were collected through interviews and document analysis and analyzed qualitatively to assess the consistency between legal norms and judicial application. The novelty of this study lies in its integrated analysis of the conflict between Article 168 of the Indonesian Criminal Procedure Code (KUHAP), which limits testimony from family members, and its flexible application in judicial practice, particularly in cases involving child witnesses in premeditated murder. This study also contributes by combining evidentiary theory and psychological credibility analysis in assessing child testimony. The findings reveal that child witness testimony, although formally limited due to age and familial relationship, can still be considered valid when supported by corroborative evidence such as forensic reports and expert testimony. The court implicitly applied a substantive approach prioritizing material truth over rigid procedural formalism. However, judicial reasoning lacks systematic legal justification, particularly in explaining exceptions to evidentiary rules and the weight of each piece of evidence. In conclusion, the admissibility of child witnesses in criminal proceedings is not solely determined by formal legal requirements but also by their probative value and consistency with other evidence. Strengthening judicial reasoning is necessary to ensure both substantive justice and normative legitimacy in criminal adjudication.